Red-emitting hybrid based on eu3+-dbm complex anchored on silica nanoparticles surface by carboxylic acid for biomarker application - Santos, João A. O. [UNESP]; Mutti, Alessandra M. G. [UNESP]; Bispo-Jr, Airton G. [UNESP]; Pires, Ana M. [UNESP]; Lima, Sergio A. M. [UNESP] (MDPI, 2020)
Luminescent organic-inorganic hybrids containing lanthanides (Ln3+) have been prominent for applications such as luminescent bio-probes in biological assays. In this sense, a luminescent hybrid based on dense silica (SiO2) nanospheres decorated with Eu3+ β–diketonate complexes using dibenzoylmethane (Hdbm) as a luminescent antenna was developed by using a hierarchical organization in four steps: (i) anchoring of 3-aminopropyltriethoxysilane (APTES) organosilane on the SiO2 surface, (ii) formation of a carboxylic acid ligand, (iii) coordination of Eu3+ to the carboxylate groups and (iv) coordination of dbm− to Eu3+. The hybrid structure was elucidated through the correlation of thermogravimetry, silicon nuclear magnetic resonance and photoluminescence. Results indicate that the carboxylic acid-Eu3+-dbm hybrid was formed on the surface of the particles with no detectable changes on their size or shape after all the four steps (average size of 32 ± 7 nm). A surface charge of −27.8 mV was achieved for the hybrid, assuring a stable suspension in aqueous media. The Eu3+ complex provides intense red luminescence, characteristic of Eu3+ 5D0→7FJ electronic transitions, with an intrinsic emission quantum yield of 38%, even in an aqueous suspension. Therefore, the correlation of luminescence, structure, particle morphology and fluorescence microscopy images make the hybrid promising for application in bioimaging.
Keywords: Bioimaging; Functionalization; Lanthanide; Luminescent material; SiO2; β–diketone